2010
DOI: 10.2147/cia.s13813
|View full text |Cite
|
Sign up to set email alerts
|

Use of cross-linked carboxymethyl cellulose for soft-tissue augmentation: preliminary clinical studies

Abstract: Purpose:The continual search for new products for soft-tissue augmentation has in recent years led to the introduction of long lasting alternatives to hyaluronic acids and collagen that are composed of other polymers able to improve clinical persistence over time. This is the first report in which sodium carboxymethyl cellulose (CMC) has been chemically treated by the cross-linking process and thus used as a hydrogel for soft-tissue augmentation through injection with thin needles. The study evaluates, from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 18 publications
0
19
0
1
Order By: Relevance
“…Due to the merits of non-toxicity, water solubility, low-cost and environmental friendliness [25], CMC has been widely used as a natural ingredient for hydrogels, and has been developed for various applications including tissue engineering, drug delivery, wound dressing and plant breeding [24][25][26][27][28][29]. All these applications expect self-healing performance of CMC hydrogels to enhance their service life and applicability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the merits of non-toxicity, water solubility, low-cost and environmental friendliness [25], CMC has been widely used as a natural ingredient for hydrogels, and has been developed for various applications including tissue engineering, drug delivery, wound dressing and plant breeding [24][25][26][27][28][29]. All these applications expect self-healing performance of CMC hydrogels to enhance their service life and applicability.…”
Section: Introductionmentioning
confidence: 99%
“…All these applications expect self-healing performance of CMC hydrogels to enhance their service life and applicability. Currently, the preparation methods of CMC hydrogels are largely based on chemical cross-linking [24][25][26][27][28][29]. However, breaking the chemically cross-linked CMC networks results in irreversibly damaged polymer networks, and the chemical agents involved are generally toxic.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25] Carboxymethyl cellulose (CMC) is water-soluble cellulose ether, and an acid derivative of cellulose. Due to their low cost, biodegradability, and nontoxicity, cellulose and its derivatives are highly attractive biopolymers for biomedical applications as an antioxidant, 26,27 as exudates absorber near wounds, for control drug release, 28 and as cell carriers. 29 It finds applications in preventing postoperative adherences and epidural scarring.…”
Section: Introductionmentioning
confidence: 99%
“…To fabricate porous PMMA, an aqueous gel of carboxymethylcellulose (CMC) can be used in a phase separation strategy due to the hydrophobicity of PMMA and its monomer, MMA. Similar to PMMA, CMC also has been extensively used in clinical applications such as the treatment of glottic insufficiency,19 postoperative laparoscopic adhesion,20 and the augmentation of soft‐tissue 21. Fabrication of porous PMMA with CMC has been investigated for bone substitution 22–25.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to PMMA, CMC also has been extensively used in clinical applications such as the treatment of glottic insufficiency, 19 postoperative laparoscopic adhesion, 20 and the augmentation of soft-tissue. 21 Fabrication of porous PMMA with CMC has been investigated for bone substitution. [22][23][24][25] A 20-year follow-up clinical study 25 revealed good implant fixation due to bone ingrowth into pores and no side effects ascribed to the porous PMMA bone substitute.…”
Section: Introductionmentioning
confidence: 99%